FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN WAKTU MENYUSUI PERTAMA KALI PADA BAYI BARU LAHIR DI RSUD MERAUKE - Hermelina Yaru; Ngadiyono Ngadiyono; Nur Khafidhoh (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Advantages of Early Breastfeeding Initiation is to get food with quality and quantity. The purpose of this study to determine the factors associated with the time of breastfeeding the firstfirst time in newborns at the Regional General Hospital (RSUD). This research design using descriptive method of quantitative research with cross sectional approach with accidental sampling technique. The sample is 60 respondents. Data were collected in the post partum room of normal post-partum mothers with normal-born infants at RSUD Merauke. Independent variable is mother's age, mother's education, mother's parity, mother's knowledge, type of delivery and support of health officer. The dependent variable is the first feeding time in the newborn. The results showed that the factors that influence the time of first breastfeeding in the newborn is the type of labor (p value 0.00) while the non-influencing factors are maternal age (p value 0.765), maternal education (p value 0.390), maternal parity value 0.12) maternal knowledge (p value 0, 528) and health officer support (p value 0.19)